Farm-level exploration of economic and environmental impacts of sustainable intensification of rice-wheat cropping systems in the Eastern Indo-Gangetic plains - Adelhart Toorop, Roos; López Ridaura, Santiago; Bijarniya, Deepak; Kalawantawanit, Eakapat; Jat, Raj K.; Prusty, Ashish K; Jat, Mangi Lal; Groot, Jeroen C.J. (Elsevier, 2020)
Agriculture in rural Bihar needs to maintain its productivity while enhancing its biophysical sustainability. To sustainably intensify the predominant rice-wheat systems, alternative cropping patterns with short duration legumes, planted in the usually fallow summer season, were developed. The addition of the legume ensures near-permanent soil cover, breaks the cereal-cereal cycle, and aims to improve soil quality while yielding between 0.6 and 1.2 Mg ha-1 of protein-rich dry matter. On-station experiments previously demonstrated the agronomical feasibility of the alternative cropping patterns while this study addresses the implications of such field-level changes at farm-level for different types of smallholders. We used the model FarmDESIGN to 1) assess current farm performance, 2) explore options to rearrange cropping patterns and 3) assess the impact of cropping patterns with mung bean. We found diverse farm performances, indicating a heterogenous farming community. Re-arranging current cropping patterns gave all farms possibilities to save water, increase soil organic matter content and decrease nitrogen losses but showed trade-offs with operating profit. Higher resource endowed farms had most potential to favourably rearrange the farm and improve multiple performance indicators. Two out of the five farms assessed did not benefit from including the alternative cropping patterns. We conclude that the impact of innovations greatly depends on farm type and current farm features and performance, described by a farm typology.